The reconstruction of castles and country houses after around 1600, focusing on the 'Huis te Capelle' near Rotterdam (Bulletin KNOB, 2005)
In the beginning of the Dutch war of independence (1568-1648) it was particularly the countryside that suffered. When around 1590 many towns had obtained a new confirmation, the attention for architecture revived again (ill. 1-5). The ornamental roof played an important part in this.It originated in around 1550 by a clear separation between roof and facade by means of a gutter board. The place of the chimney was also given more attention. For a long time building in the countryside proceeded cautiously, in small parts. Consequently, the reconstruction of country houses was not a major chapter in Dutch history of architecture, which had taken cover in the towns.Restoration in the countryside did not start until 1609, when a truce with Spain was concluded. After this truce the nobility, who had fled to the south, were able to sell their confiscated property. For the greater part this property passed into the hands of townsmen, who preferred country houses to castles. In the first phase of restoration, building was modest and improvised (ill. 6, 7). Often in various successive campaigns.For that reason, the facades remained old fashioned. In the last phase a fashionable ornamental roof was often applied (ill. 9-11). A project which took a central place in this was the Huis te Capelle, which rose again in 1610 and was completely refurbished in 1617 (ill. 12-16).The culmination of this new form of country houses with ornamental roofs was the first wing of the castle Honselaarsdijk, built by order of Frederik Hendrik (ill. 17). In that same year the war against Spain was resumed, which tempered the desire to build large country houses again (ill. 18).After the situation had become safer around 1635, the masterpieces from the period of the Truce were reverted to again in new projects (ill. 19-23), although the details were simplified. The great and successful models of the country houses with ornamental roofs lived on in imitations of their main form or of components. They were a welcome change in severe Dutch Classicism.